Growth Inhibitory Activity of Callicarpa americana Leaf Extracts Against Cutibacterium acnes - Pineau, Rozenn M.; Hanson, Sarah E.; Lyles, James T.; Quave, Cassandra L. (Frontiers in Pharmacology, 2019)
Acne vulgaris is a common skin disease affecting adolescents and young adults of all ethnic groups, negatively impacting self-esteem, self-confidence and social life. The Gram-positive bacteria Cutibacterium acnes colonizes the sebum-rich follicle and contributes to inflammation of the pilosebaceous gland. Long-term antibiotic therapies targeting C. acnes lead to the development of antimicrobial resistance, and novel acne vulgaris therapies are needed. This study investigated the C. acnes inhibitory activity of Callicarpa americana leaves, a native Southeastern United States shrub historically used by Native Americans to treat fever, stomachache, and pruritis. Flash chromatography fractions of the ethyl acetate soluble C. americana ethanol leaf extract (649C-F9 and 649C-F13) exhibited MICs ranging from 16-32 µg mL-1 and IC50 range of 4 to 32 μg mL-1 against a panel of 10 distinct C. acnes isolates. Cytotoxicity against an immortalized human keratinocyte cell line (HaCaTs) skin was detected at more than 8 times the dose required for growth inhibitory activity (IC50 of 256 μg mL-1 for 649C-F9 and IC50 >512 μg mL-1 for 649C-F13). This work highlights the potential of C. americana leaf extracts as a cosmeceutical ingredient for the management of acne vulgaris. Further research is necessary to assess its mechanism of action and in vivo efficacy.